Peramalan Data Time Series Seasonal Menggunakan Metode Analisis Spektral - Anis Mahfud Al’afi; Widiarti Widiarti; Dian Kurniasari; Mustofa Usman (Jurnal Siger Matematika, 2020)
Air transportation is now a mode of transportation that is often the first choice. Although the transportation costs are relatively expensive, it can save a lot of time to get to the destination. Therefore, predicting the number of aircraft passengers is an interesting thing to study. In this study forecasting the number of aircraft passengers at Raden Intan II Airport using spectral analysis methods. Spectral analysis is used to obtain more complete information about the time series data characteristics to examine the periodicity. After getting the periodicity the data is modeled using the ARIMA Seasonal Method. Based on the analysis results it is known that the best model for forecasting aircraft passengers at Raden Intan II Airport is Seasonal ARIMA (0,1,1) (0,1,1)3